Value co-creation through social media: a case study of a start-up company - Kim, Junic; Choi, Hwanho (Journal of Business Economics and Management, 2019)
This research examines social media users’ value-creation processes and the drivers of a start-up company’s successful social media strategy. This research primarily aims to understand start-ups’ effective utilization of social media and value co-creation processes. Although utilizing social media has become key for many organizations, start-ups and small businesses often suffer from a lack of understanding and knowledge of the utilization of social media tools. Therefore, this article uses a case study on the relationship between a social media platform and users’ value co-creation to offer a conceptual framework for start-ups to consider in utilizing social media. Our research reveals that four core drivers of social media success include experience, satisfaction, expression, and sharing ability. Each of these drivers in turn contains conditions for understanding users’ value-creation process and the creation of drivers for successful social media strategies. The research contributes to literature by providing a detailed review of users’ value co-creation as a part of a start-up’s successful social media strategy.